A 68-year-old Caucasian man presenting with urinary bladder lymphoepithelioma: a case report - Spinelli, Gian Paolo (BioMed Central, 2013)
INTRODUCTION: Lymphoepithelioma is a very rare form of malignant tumor originating from epithelial line cells. Its occurrence has potential clinical, therapeutic and prognostic implications. In the present report we describe an unusual case of bladder cancer with two different histological varieties: transition cell carcinoma and lymphoepithelioma-like carcinoma. Lymphoepithelioma-like carcinoma of the bladder has only been rarely reported in the literature to date. CASE PRESENTATION: We present the case of a 68-year-old Caucasian man who, after occurrence of hematuria, underwent transurethral resection of a bladder tumor. The results of a histological examination confirmed a high-grade non-muscle-invasive pT1 lymphoepithelioma-like carcinoma of the urinary bladder, associated with a concurrent high-grade transition cell carcinoma. After analyzing the histological features, our patient was subjected to treatment with intra-vesical instillations of bacillus Calmette-Guérin. Our work stresses that diagnosis and therapeutic approaches can be difficult and controversial, especially in the early stages of this rare carcinoma. CONCLUSIONS: This report emphasizes the importance of extending our knowledge and experiences regarding this uncommon carcinoma. Further studies are needed to better understand this rare disease and define more accurate diagnostic and therapeutic strategies.